2012
DOI: 10.1007/s10535-012-0239-3
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of eight cytosolic sHSP genes and their expression in Capsella bursa-pastoris

Abstract: Small heat shock proteins (sHSPs) are crucial components of the plant response to heat shock. We identified and analyzed eight sHSP genes of Capsella bursa-pastoris to better understand the ability of this species to adapt. Eight genes were initially cloned and sequenced from the mature embryo cDNA pool. They belong to the cytosolic I (CI), cytosolic II (CII), and cytosolic III (CIII) subfamilies. One CI sHSP gene was homologous to that of C. rubella. Sequence analysis using 3'RACE revealed that there are two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…However, paralogous sHSP genes showed different expression levels; for example, the transcriptional level of Br22.0 MT in different organs and across embryonic stages was at least three times higher than that of Br18.0 MT. Tao et al (2012) compared the expression of two paralogous C-II sHSP genes (CbHSPCIIa and CbHSPCIIb) and likewise found that the expression of CbHSPCIIa was approximately five times higher than that of CbHSPCIIb in different organs and across embryonic stages. Br18.0A I, Br18.0B I, and Br17.1 were not expressed in any organs.…”
Section: Discussionmentioning
confidence: 99%
“…However, paralogous sHSP genes showed different expression levels; for example, the transcriptional level of Br22.0 MT in different organs and across embryonic stages was at least three times higher than that of Br18.0 MT. Tao et al (2012) compared the expression of two paralogous C-II sHSP genes (CbHSPCIIa and CbHSPCIIb) and likewise found that the expression of CbHSPCIIa was approximately five times higher than that of CbHSPCIIb in different organs and across embryonic stages. Br18.0A I, Br18.0B I, and Br17.1 were not expressed in any organs.…”
Section: Discussionmentioning
confidence: 99%